Football as an agent or tool to promote women and girls' empowerment: a case study of coaching for hope - Cape Town - Chiyapo, Tebogo (Department of Sociology, 2014)
Football has been used as a tool for empowering women in numerous countries across the globe. This qualitative case study critically assesses the viability of football as an agent for empowering females. The study is based on Coaching for Hope's, "Empowerment of Women and Girls through Football" programme. Coaching for Hope (CFH) uses football as a vehicle to address issues, such as HIV/AIDS, drug and substance abuse, gender equity and other problems facing youth. CFH has partnered with a range of sports organisations which are committed to bring about social change through this programme. These organisations use sport as a means of engaging with, and supporting the upliftment of young people, who live in challenging social circumstances. The evidence, which has been distilled from numerous interviews, observations and documentary analyses in this study, indicates that women's participation in football activities is hampered by a number of factors. Previous studies note that gender blockages have deprived women and girls from taking an active part in football. Women face social, economic, cultural and educational challenges that ultimately hamper their empowerment process and which need to be addressed. Other challenges faced by women and girls include, social prejudice, religious issues, as well as gender domination. The findings of this thesis support these claims. The findings also point to the conclusion that participating in football is perceived to have a positive impact in health, community development, team building and problem solving. The respondents stated what they saw as the necessary conditions for sport to have beneficial outcomes. For example, the need for the programme to have clear goals and objectives, as well as effective plans for implementing and monitoring activities were some of the crucial conditions mentioned by the respondents. Their argument is that if you understand what you want to achieve and how you might achieve it, you will be able to design a programme that will yield the desired outcomes. These are the reasons for treating this project as sport for development project. Sport for development is conceptually different to sport development as it focuses more on human development rather than the techniques of the game. This study also looked at the participants' perceptions of how the programme is contributing to their empowerment. Empowerment is a key area that has a contested definition in development literature. The women and girls interviewed also have differing views about the nature of empowerment. Some of the most common outcomes were perceived improvements in their self-esteem, self-confidence self-awareness and leadership abilities, and tolerance of social circumstances. The evidence shows that the programme is not about football or any particular sport, rather, it is about the processes and experiences generated from playing a sport. It is evident from this research that sport for development has the potential to empower women and girls in an informal and fun way that encourages personal growth. Participation in football does not have a causal effect on empowerment;; rather, there is a need for systems which facilitate the empowerment process.